2008
DOI: 10.1073/pnas.0804453105
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the complex between programmed death-1 (PD-1) and its ligand PD-L2

Abstract: Programmed death-1 (PD-1) is a member of the CD28/B7 superfamily that delivers negative signals upon interaction with its two ligands, PD-L1 or PD-L2. The high-resolution crystal structure of the complex formed by the complete ectodomains of murine PD-1 and PD-L2 revealed a 1:1 receptor:ligand stoichiometry and displayed a binding interface and overall molecular organization distinct from that observed in the CTLA-4/B7 inhibitory complexes. Furthermore, our structure also provides insights into the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
198
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(213 citation statements)
references
References 29 publications
12
198
2
1
Order By: Relevance
“…The molecule is well defined by electron density, safe for a region between C′D strands. However, previous reports done by Lázár [4,5,6] .…”
Section: Structure Of the Pdl-1contrasting
confidence: 40%
“…The molecule is well defined by electron density, safe for a region between C′D strands. However, previous reports done by Lázár [4,5,6] .…”
Section: Structure Of the Pdl-1contrasting
confidence: 40%
“…S2A). Previous studies identified several human PD-1 residues as critical for PD-L1 and PD-L2 binding (31)(32)(33)(34), and these residues are contained within the two sequences (Supplementary Fig. S2B).…”
Section: Binding Analysis Of Nivolumab and Inhibition Of Ligand Bindingmentioning
confidence: 99%
“…Eight of 14 aa involved in binding to PD-1 are identical or highly conserved between PD-L1 and PD-L2. Trp-110 in the middle of the G strand of PD-L2 is an Ala in PD-L1, and mutational analysis suggests that this accounts for much of the 3-fold-higher affinity of PD-L2 for PD-1 (6,14). Binding face to face establishes an acute angle between PD-1 and PD-L1 or PD-L2, as opposed to the right angle between CTLA4 and B7-1.…”
mentioning
confidence: 99%
“…The role of the PD-1 pathway in peripheral T cell tolerance and its role in immune evasion by tumors and chronic infections make the PD-1 pathway a promising therapeutic target. Two recent papers have determined the structures of the PD-1/PD-L1 (5) and PD-1/PD-L2 complexes [see Lazar-Molnar et al (6) in this issue of PNAS].…”
mentioning
confidence: 99%